(untitled) (Journal of Kidney Cancer, 2024)
This report recounts the diagnostic workup of a pediatric female who presented with hematuria secondary to a large renal mass visualized on abdominal imaging. Histologic assessment and subsequent immunohistochemistry studies were performed. Intense, unequivocal immunohistochemical expression of TFE3 and alpha-methylacyl-CoA-racemase with corresponding negativity for carbonic anhydrase IX, along with highly distinctive clinical, radiologic, gross, and microscopic findings confirmed the diagnosis of a renal cell carcinoma with TFE3 gene rearrangement – the first ever reported case in the Philippines. This case highlights the vital role and significant diagnostic impact of reliable, affordable and accessible immunohistochemistry studies in low-resource settings where molecular modalities for evaluating rare diseases are largely unavailable. Recognition of distinctive morphologic, immunohistochemical, and cytogenetic features in childhood and adolescent renal malignancies allows for the timely institution of therapeutic interventions for this aggressive entity.